Fc-enhanced anti-CCR6 antibody elicits robust therapeutic effects across multiple autoimmune diseases - Alam, Md Jahangir; Yap, Yu-Anne; Ang, Caroline; Xie, Liang; Shane, Hillary L.; Mackay, Charles R.; Robert, Remy (Frontiers in Immunology, 2026)
Activation of the chemokine receptor CCR6 orchestrates the trafficking of IL-17-producing pathogenic immune cells to the sites of inflammation, thus contributing to the development of numerous inflammatory and autoimmune diseases. As such, CCR6 has emerged as a promising therapeutic target for treating Th17-mediated inflammatory disorders. In this study, we employed a targeted strategy, which we termed ‘immunological surgery’, using an Fc-engineered anti-human CCR6 monoclonal antibody (αhCCR6 DLE-mut mAb) designed to engage effector mechanisms against CCR6+ immune cells and deplete them. We evaluated the therapeutic efficacy of this approach in preclinical mouse models of representative autoimmune conditions, including scleroderma, psoriasis, and rheumatoid arthritis. Selective targeting of CCR6+ cells with αhCCR6 DLE-mut mAb exhibited remarkable efficacy in reducing established inflammation across all disease models. In a bleomycin-induced scleroderma model, αhCCR6 mAb treatment markedly reduced dermal thickening and attenuated scleroderma-associated lung inflammation and fibrosis. In the imiquimod-induced psoriasis model, administration of αhCCR6 mAb led to significant reductions in skin thickening, epidermal hyperplasia, and dermal immune cell infiltration. Similarly, in the collagen-induced arthritis (CIA) model, αhCCR6 mAb treatment significantly alleviated all signs of joint inflammation. Thus, our findings demonstrated that CCR6-targeted therapy could be a promising and effective approach for the treatment of Th17-mediated inflammatory disorders. Moreover, we believe this approach may overcome the challenge of chemokine receptor redundancy by leveraging receptor-specific signatures to eliminate pathogenic leukocyte subsets with high precision.